The influence of work stress, financial problem and family-work conflict toward job performance among Malaysia Army personnel - Nor Azizi, Mohd Adam (2024)
The increasing demands and challenges faced by military personnel globally highlight the need to understand factors influencing their job performance, particularly in high-stress environments. This study examines the impact of work stress, financial problems, and family-work conflict on the job performance of Malaysian Army personnel. Data were collected from 204 personnel of the 73rd Battalion Royal Service Corps in Terendak Camp, Melaka, using structured questionnaires, and analyzed through descriptive statistics and normality using SPSS version 30 and Partial Least Squares Structural Equation Modeling (PLS-SEM) SmartPLS 4.0 to assess the measurement and structural models. The result show that financial problem significantly influenced the Malaysian Army personal job performance, whereas, the work stress and family-work conflict proven insignificant. The study underscores the complexity of stress-performance dynamics within military contexts and highlights the importance of exploring additional underlying mechanisms in future research to enhance the well-being and operationalreadiness of army personnel